Caracterização de estoques naturais de três espécies de Gymnotus (Gymnotiformes: Gymnotidae) exploradas como iscas vivas em cinco localidades do Pantanal - Braga, Gisele da Silva Ferreira (2016)
Gymnotus is the most representative genre from the Gymnotidae family with 41 species formally described. Popularly known as electric fishes or “tuviras” they represent a major live bait source among watersheds in Latin America. In the region of the Pantanal of Mato Grosso and Mato Grosso do Sul it is an important economic resource in fishery for being an excellent bait; adding an high trade value in these regions. Species of this group presents some peculiar traits. In special, an oblong body shape, coloring patterns and an organ that emits shockwaves which are utilized for communication, orientation and group identification. However, morphological similarities between species troubles the taxonomic questions of these organisms group. Based on this, the present work has the objective to characterize the commercial natural livestock of Gymnotus traded as live baits in Pantanal of Mato Grosso and Mato Grosso do Sul by using data from cytogenetic, genetic, morphometric and color pattern of the samples. 242 sequences from barcode gene COI was analyzed by dendrogram using genetic distance (Neighbor Joining - NJ) and haplotype network. A principal component analysis (PCA) was performed from 14 features measures of a group of 66 species suggested from the NJ results. The genetic and morphometric analyses exhibit 3 distincts taxonomic groups of Gymnotus to region of study: Gymnotus paraguensis, Gymnotus pantanal and Gymnotus sylvius. The results shows Gymnotus paraguensis as the most abundant (84.4%) and Gymnotus pantanal as the lesser one (7%). The genetic divergence between groups was: Gymnotus paraguensis vs G. sylvius = 5.9%; G. paraguensis vs G. pantanal = 7.8% and G. sylvius vs G. pantanal = 8.5%. The haplotype network showed a moderate organization for Gymnotus paraguensis and a possible faunal regionalization. The coloring analyses revealed a homogenous general pattern of stripes in Gymnotus sylvius and Gymnotus pantanal and conspicuous variations between species of Gymnotus paraguensis. These results have shown fragility on taxonomic studies of the group and major importance on integration of chromosomal, genetic and molecular biology data to better distinguish Gymnotus specially found in the Pantanal of Mato Grosso.